Letter - Borough of Paddington Labour Party and Trades Council, 10 May 1926 (Paddington)
1926-05-10 "Letter - Borough of Paddington Labour Party and Trades Council, 10 May 1926" [g0215001.jpg], 10 May 1926 Local Organisation